Alectinib, an Anaplastic Lymphoma Kinase Inhibitor, Abolishes ALK Activity and Growth in ALK-Positive Neuroblastoma Cells - Alam, Muhammad Wasi; Borenäs, Marcus; Lind, Dan E.; Cervantes-Madrid, Diana; Umapathy, Ganesh; Palmer, Ruth H.; Hallberg, Bengt (Frontiers in Oncology, 2019)
Oncogenic receptor tyrosine kinases including anaplastic lymphoma kinase (ALK) are implicated in numerous solid and hematologic cancers. ALK mutations are reported in an estimated 9% of neuroblastoma and recent reports indicate that the percentage of ALK-positive cases increases in the relapsed patient population. Initial clinical trial results have shown that it is difficult to inhibit growth of ALK positive neuroblastoma with crizotinib, motivating investigation of next generation ALK inhibitors with higher affinity for ALK. Here, alectinib, a potent next generation ALK inhibitor with antitumor activity was investigated in ALK-driven neuroblastoma models. Employing neuroblastoma cell lines and mouse xenografts we show a clear and efficient inhibition of ALK activity by alectinib. Inhibition of ALK activity was observed in vitro employing a set of different constitutively active ALK variants in biochemical assays. The results suggest that alectinib is an effective inhibitor of ALK kinase activity in ALK addicted neuroblastoma and should be considered as a potential future therapeutic option for ALK-positive neuroblastoma patients alone or in combination with other treatments.